The use of antidepressants and the risk of haemorrhagic stroke: a nested case control study - Douglas, Ian; Smeeth, Liam; Irvine, David (British journal of clinical pharmacology, 2011)
WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Selective serotonin re‐uptake inhibitors (SSRI) are associated with an increased risk of bleeding disorders at a number of sites. • It is currently unclear whether they increase the risk of haemorrhagic stroke, with conflicting results reported. WHAT THIS STUDY ADDS • We found no association between SSRI use and haemorrhagic stroke. • The large number of patients involved in the study allowed us to rule out any substantial effect. • The results were similar in people with and without a previous history of cerebrovascular events. AIM To investigate whether selective serotonin re‐uptake inhibitor (SSRI) use is associated with an increased risk of haemorrhagic stroke in a cohort of antidepressant users. METHODS We conducted a case control study, nested within a cohort of antidepressant users in the United Kingdom General Practice Research Database. A cohort of 365 195 patients prescribed either an SSRI or tricyclic antidepressant between 1992 and 2006 was identified. Three hundred and fifty‐seven cases of haemorrhagic stroke were observed and 1631 control patients without haemorrhagic stroke were selected. RESULTS The primary analysis showed no evidence of an association between current SSRI or TCA use and haemorrhagic stroke. Current use of an SSRI compared with no use at the time of haemorrhagic stroke was associated with an adjusted odds ratio of 1.11 (95% confidence interval (CI) 0.82, 1.50). For current tricyclic use the equivalent odds ratio was 0.73 (0.52, 1.02). There was no evidence that prior cerebrovascular events modified the effect of either SSRIs or TCAs. CONCLUSIONS We found no evidence that SSRIs are associated with an increased risk of haemorrhagic stroke, regardless of prior history of cerebrovascular events.